An examination of cutting-edge developments in Bamboo-PLA composite research: A comprehensive review - Khan A.; Sapuan S.M.; Yusuf J.; Siddiqui V.U.; Zainudin E.S.; Zuhri M.Y.M.; Tuah Baharuddin B.T.H.; Ansari M.A.; Rahman A.A.A. (Elsevier Ltd, 2024)
The development of environmentally friendly composite materials that may be used in a variety of applications is the result of growing environmental concerns and imminent depletion of petroleum-based resources. The use of bio-based polymers that are reinforced with natural fibers has emerged as an effective alternative to synthetic fiber-reinforced polymers for the fabrication of composites. Bamboo has grown in popularity as a natural fiber because it is easily accessible, inexpensive, biodegradable, and has excellent mechanical characteristics. This review covers topics including the extraction of bamboo fiber and modification techniques of bamboo/polylactic acid (PLA) composites, challenges in their interfacial interaction, potential solutions to incompatibility issues, and applications of bamboo/PLA composites. In order to boost the mechanical, flame-retardant, and UV-shielding characteristics of bamboo fiber and PLA, the interfacial interaction between them is essential. This review also highlights several areas that may need more research and offers a comprehensive overview of the potential uses of bamboo/PLA composites. This article provides significant insights and suggestions for researchers and experts involved in the green composites field that can lead to the development of sustainable materials for a range of applications. 2023 Elsevier Ltd